2020
DOI: 10.1080/17430437.2020.1814572
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of ‘Ireland’, sport and identity: the craft of doing sociology

Abstract: Eric Dunning influenced the development of curricula and research agendas in sociology, history, social science and sports studies, internationally, in the UK and in Ireland. Dunning was also doctoral supervisor to, and academic colleague/mentor and friend of, both authors (at Leicester, Dublin and Chester). Inspired by him, this paper reflects on the craft of sociological research. The case study is the struggle for recognition of 'Ireland' in international athletics and the associated painstaking ongoing arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The place of sport in regard to the rise or resurgence in national consciousness amongst contemporary Europeans is significant since this extremely popular social practice has the power to both unite and divide large numbers of citizens. Recent figurational studies have demonstrated this to be the case (see for example Liston and Deighan 2019;Liston and Kitching 2020;Liston and Maguire 2020). Throughout the history of British sport one can observe division between the nations of the UK (England, Scotland, Wales and Northern Ireland) in terms of the organisation of international sporting contests, including for instance, football, cricket and rugby World Cups as well as the Commonwealth Games.…”
Section: Using Elias's Drag-effect To Understand the Relationship Between Contemporary English National Identity And Sportmentioning
confidence: 99%
“…The place of sport in regard to the rise or resurgence in national consciousness amongst contemporary Europeans is significant since this extremely popular social practice has the power to both unite and divide large numbers of citizens. Recent figurational studies have demonstrated this to be the case (see for example Liston and Deighan 2019;Liston and Kitching 2020;Liston and Maguire 2020). Throughout the history of British sport one can observe division between the nations of the UK (England, Scotland, Wales and Northern Ireland) in terms of the organisation of international sporting contests, including for instance, football, cricket and rugby World Cups as well as the Commonwealth Games.…”
Section: Using Elias's Drag-effect To Understand the Relationship Between Contemporary English National Identity And Sportmentioning
confidence: 99%
“…This diplomacy was a new phase in Irish-British relations, involving official and non-state diplomats. Travelling in the same direction, there were differences in emphasis in their practice of statecraft, including the practice of sportcraft (Liston and Maguire, 2020).…”
Section: The 'Great Game' Of Irish-british Relationsmentioning
confidence: 99%
“…Yet Burghley and Holt ensured, via Australian organizers, that EIR was displayed on the athletics scoreboard for Irishman Ronnie Delany's gold medal win in the 1500 metres, and GBI (not GBR) for British runner, Hewson (Liston and Maguire, 2020).…”
Section: Collusion Soft Power and Sportcraftmentioning
confidence: 99%
See 2 more Smart Citations